PENGARUH BUDAYA ORGANISASI, INTELLECTUAL CAPITAL DAN KERAGAMAN PENGUKURAN KINERJAN TERHADAP KINERJA ORGANISASI (STUDY EMPIRIS PERUSAHAAN MANUFAKTUR DI PROVINSI BANTEN ) - Amrullah, Rahadian; Ismail, Tubagus; Uzliawati, Lia (JURNAL RISET AKUNTANSI TIRTAYASA, 2018)
This study aims to find empirical evidence on the influence of Organizational Culture, Intellectual Capital, and Diversity of Performance Measurement on the performance of the Organization. Sampling method used in this study is the method of purposive sampling and obtained sample research of 60 manufacturing companies as an observation item contained in Banten Province. Data were analyzed using Partial Least Square (PLS) software. The results of this study indicate that the (1) organizational culture has a positive and significant influence on the organizational performance, (2) organizational culture variables have positive and significant effect on Intellectual capital, (3) Intellectual Capital has a positive and significant influence on the diversity performance measurement, (4) diversity performance measurement have positive and significant influence to organizational performance, (5) Intellectual Capital negative affects organizational performance and (6) Intellectual Capital positivelyaffects organizational performance mediated by Diversity Performance measurement.Keywords: Organizational Culture, Intellectual Capital, Diversity of PerformanceÂ Measurement, Organizational Performance